The impact of the cardiac rehabilitation program in patients with mid-range heart failure (40-50%) in improving cardio respiratory predictors. (29th July 2021) - Rodrigues, HR; Ferreira, V; Alves, L; Sousa, D; Pinto, J; Pinto, A; Rio, P; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Centro Hospitalar Universitário Lisboa Central Methods: We studied 30 patients (P) with ejection fraction (EF) 40-50%, in a number of 198 P that participated in cardiac rehabilitation program (CRP). Of these P, 24 (80%) male and 6 (20%) female, 20 P were diagnosed myocardial infarction with ST-segment elevation, 2 P myocardial infarction non ST and 8 P with myocardial hypertrophy non ischemic. Of these P 30% were diabetics, 56% hypertension, 70% dyslipidemia, 36% smokers previous to CRP and body mass index 26, 3 medium. All P were submitted to previous echocardiogram, cardiopulmonary exercise testing (CET) and a rehabilitation program minimum 4 sessions and maximum 52 sessions. At the end of the total sessions the echocardiogram and CET were repeated. Results: Of the 30 P that participated in CRP only 20 completed the program, while the other 10 P dropped out because of social and economic problems. Of the P that completed the CRP, 70% got better on EF, 80% improved VE/VCO2 slope < 33 therefore are classified VC-II in ventilatory classification (VC), 5% VE/VCO2 slope > 40 VC-III classification, and 15% maintained the initial classification. 50% of the P increased at least one level metabolic equivalent of task (MET) from the first CET. Only 3 of the 20 patients came, once, to the hospital after the CRP with heart failure, and one died but did not fulfill the program. Conclusion: Patients with mid-range heart failure submitted to a CRP can improve cardiorespiratory predictors, leading to a better quality of life. However, it is important to find solutions to minimize the causes that make patients to give up CRP.